2014
DOI: 10.1007/s00343-015-4205-8
|View full text |Cite
|
Sign up to set email alerts
|

Food web structure and trophic levels in polyculture rice-crab fields

Abstract: Stable carbon and nitrogen isotopes were used to investigate nutrient pathways and trophic relationships from the rice-crab system in Panjin, Liaoning Province, China. Values of δ 13 C ranged from -27.38‰±0.44‰ to -18.34‰±0.26‰ and δ 15 N ranged from 1.10‰±0.88‰ to 9.33‰±0.57‰. Pseudorasbora parva (Stone moroko) had the highest δ 13 C and δ 15 N values. The lowest δ 13 C values were obtained for the macrophytes and the lowest δ 15 N value was found in sediments. Stable carbon and nitrogen isotopes were used to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Although a high protein diet can effectively promote the growth performance and digestive physiology level of mitten crab, it can decrease soil pH from the rice-crab coculture system and negatively impact soil bacteria community diversity. Moreover, formulated feed does not make up a larger portion of the diet of E. sinensis , and excess formulated feed added to the rice-crab system sinks to the bottom of field, which may lead to water pollution ( Guo et al, 2015 ). Therefore, a lower dietary protein level such as ca.…”
Section: Discussionmentioning
confidence: 99%
“…Although a high protein diet can effectively promote the growth performance and digestive physiology level of mitten crab, it can decrease soil pH from the rice-crab coculture system and negatively impact soil bacteria community diversity. Moreover, formulated feed does not make up a larger portion of the diet of E. sinensis , and excess formulated feed added to the rice-crab system sinks to the bottom of field, which may lead to water pollution ( Guo et al, 2015 ). Therefore, a lower dietary protein level such as ca.…”
Section: Discussionmentioning
confidence: 99%
“…Hu et al 52 determined that the crab‐rice coculture environment significantly reduced the rate of precocious crab development and enhanced their economic value. Guo et al 53 demonstrated that crabs prey on phytoplankton, algae, zooplankton, weeds and benthic invertebrates in paddy fields. Analyzing crab diets with isotopic 13 C and 15 N, Hu et al 52 found that approximately 59.1% of food ingested by crabs originated from these organisms rather than artificial crab feed, indicating that crabs fully utilize food resources present in the rice‐crab coculture system without supplementation.…”
Section: Effect Of Rice‐crab Symbiosis On Organisms In the Systemmentioning
confidence: 99%
“…It can reduce fertilizer use by over 30% and pesticide use by 50%, and significantly improve rice quality in terms of no herbicide and less pesticide used, and increasing coarse rice rate, head rice rate, gel consistency, and chalkiness rate of grain quality in rice-duck production systems, compared with the conventional farming model (Huang et al 2014). The ongoing exploration of coculture models means new co-culture models in the rice ecosystem regularly appear, like rice-crab (Guo et al 2015), ricecrayfish (Jiang and Cao 2021), rice-soft shelled turtle (Zhang et al 2016b), and rice-frog (Fang et al 2021) (Fig. 3).…”
Section: Agroecological Intensification By Co-culture Systemsmentioning
confidence: 99%